1984
DOI: 10.1073/pnas.81.20.6432
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of mutations affecting the cII activation site at the PRE promoter of bacteriophage lambda.

Abstract: AbQrtive initiation and run-off transcription assays were used to study the effects of cy mutations on activation of the phage X PRE promoter by cI gene product. Six point mutations in the repeated T-T-G-C sequences that flank the -35 consensus region of PRE decreased the apparent affinity of the promoter for cIe protein by -factors of 4-16 relative to tjie wild-type affinity. Fig. 1) is that its -10 region agrees with the corresponding consensus promoter sequence (T-A-T-A-A-T) at only three of six sites, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In a cell following the lysogenic pathway, CI is initially expressed from the strong promoter P RE , rather than P RM (24). P RE is regulated by the phage CII protein (24,25). We expect the level of CI provided by P RE to be approximately the same in wild type and JL516.…”
Section: Discussionmentioning
confidence: 99%
“…In a cell following the lysogenic pathway, CI is initially expressed from the strong promoter P RE , rather than P RM (24). P RE is regulated by the phage CII protein (24,25). We expect the level of CI provided by P RE to be approximately the same in wild type and JL516.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro transcriptions. The runoff transcription assay was performed in 25 l of the same transcription buffer used in the footprinting experiments with the addition of 50 g of heparin per ml and 200 M nucleoside triphosphates, following published procedures (22), except that dithiothreitol was found to inhibit MetR activation and therefore was omitted. Template DNA (final concentration, 2 to 3 nM) was allowed to bind to MetR protein in the presence or absence of 2 mM D,L-homocysteine.…”
Section: Methodsmentioning
confidence: 99%
“…Presumably, other CII or CII-like proteins from lambdoid phages also have a closely similar sequence for CII binding. It has been shown that the change of one base in either of the tetrad repeats, although resulting in reduced CII binding and impaired lysogenicity, may be tolerated (43). The C1 protein of P22 (which is analogous to CII) recognizes the T-T-G-C-N 6 -T-T-G-T sequence present in p E of P22 (44,45).…”
Section: Resultsmentioning
confidence: 99%